1991
DOI: 10.1056/nejm199104183241604
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Prion Protein in Libyan Jews with Creutzfeldt–Jakob Disease

Abstract: The codon 200 lysine mutation of the prion-protein gene is consistently present among Libyan Jews with Creutzfeldt-Jakob disease, strongly supporting a genetic pathogenesis of their illness. The similarity of the clinical courses of the patient homozygous for this mutation and the patients heterozygous for it argues that familial Creutzfeldt-Jakob disease is a true dominant disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
123
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(127 citation statements)
references
References 33 publications
2
123
0
2
Order By: Relevance
“…Although amyloid-containing prion plaques are virtually absent in a number of prion diseases Hsiao et al, 1991;McKinley et al, 1991), their presence in others (Gajdusek, 1977;Ghetti et al, 1989Ghetti et al, , 1996Goldfarb et al, 1993;Tagliavini et al, 1994) suggests that the structural feature may be important in the pathology of a subset of the prion diseases. We used two synthetic prion peptides as model systems with which to examine the role of peptide ␤-sheet and amyloid content in the toxicity and membrane binding affinity of the peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Although amyloid-containing prion plaques are virtually absent in a number of prion diseases Hsiao et al, 1991;McKinley et al, 1991), their presence in others (Gajdusek, 1977;Ghetti et al, 1989Ghetti et al, , 1996Goldfarb et al, 1993;Tagliavini et al, 1994) suggests that the structural feature may be important in the pathology of a subset of the prion diseases. We used two synthetic prion peptides as model systems with which to examine the role of peptide ␤-sheet and amyloid content in the toxicity and membrane binding affinity of the peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that Mo.E199K PrP, as well as heterologous hamster and hamster/ mouse chimeric PrPs, but not MHM2.del23-88 PrP, could rescue Ngsk Prnp 0/0 mice from Purkinje cell death. Mo.E199K represents the E200K substitution in human PrP, which is commonly found in patients with familial Creutzfeldt-Jakob disease (21). The successful rescue by Mo.E199K strongly indicates that the mutant retains the major aspects of normal PrP function and thus argues against a dominant-negative role for the mutant.…”
Section: D E and F)mentioning
confidence: 99%
“…MH2M PrP has five amino acid substitutions (L108M, V111M, I138M, Y154N, and S169N) from Mo.PrP. The E199K substitution in Mo.E199K PrP corresponds to that found in patients with familial Creutzfeldt-Jakob disease (21). Offspring carrying the transgenes were identified by PCR of tail DNA as described previously (5).…”
mentioning
confidence: 99%
“…This finding prompted some investigators to propose that the Libyan Jews had contracted CJD by eating lightly cooked brain from scrapie-infected sheep when they lived in Tripoli prior to emigration. Subsequently, the Libyan Jewish patients were all found to carry a mutation at codon 200 in their prion protein (PrP) gene (14)(15)(16).…”
mentioning
confidence: 99%